2021
DOI: 10.14505//jemt.v12.4(52).16
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Brand Engagement and Brand Communications on Destination Brand Equity Maritine Tourism in Indonesia

Abstract: This study aimed to understand the influence of consumer-brand engagement and brand communication on destination brand equity, survey to maritime tourism of Ujung Kulon and Anak Krakatau, Banten. The population chosen in this study is the Instagram followers of Ujung Kulon and Krakatau Banten.The total of the samples are 96 respondents chosen using purposive sampling. This study used inferential statistic tests, which were divided into two: The correlation Test and Linear Regression Test. This study used a cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…The concept has been established as a critical component of brand equity, since it is the first stage in establishing and growing brand equity (Mansur et al, 2021). Further, Aaker (1996) elucidated it as the brand presence in consumers' mind, that is, the consumers' ability to recognise and remember a brand.…”
Section: Hypotheses Development Heritage Brand Awareness and Revisit ...mentioning
confidence: 99%
“…The concept has been established as a critical component of brand equity, since it is the first stage in establishing and growing brand equity (Mansur et al, 2021). Further, Aaker (1996) elucidated it as the brand presence in consumers' mind, that is, the consumers' ability to recognise and remember a brand.…”
Section: Hypotheses Development Heritage Brand Awareness and Revisit ...mentioning
confidence: 99%
“…This is directly related to policy indicators and governance responsibilities, namely the legal framework must be generally accepted and prioritize balance, as well as the establishment of good communication patterns between fellow members of the organization and stakeholders. Good communication patterns can also improve the reputation of the organization to stakeholders (Mansur et al, 2021a, Mansur et al, 2021b.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Schivinski et al (2022) found that social media brand-related communications were positively related to the consumer-based brand equity of fashion brands and that both relationships were moderated by self-congruity. Mansur et al (2021) discovered that marketing communication activities on Instagram added significantly to destination brand equity owing to the strong effects of its entertainment and interaction dimensions on tourist loyalty. Similarly, the study of Kurnianto and Dhewi (2022) recently showed that social media marketing influenced destination brand equity through electronic word-of-mouth.…”
Section: Conceptual Framework and Research Modelmentioning
confidence: 99%